Volcanic Eruptions and Their Repose, Unrest, Precursors, and Timing - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Volcanic eruptions are common, with more than 50 volcanic eruptions in the United States alone in the past 31 years. These eruptions can have devastating economic and social consequences, even at great distances from the volcano. Fortunately many eruptions are preceded by unrest that can be detected using ground, airborne, and spaceborne instruments. Data from these instruments, combined with basic understanding of how volcanoes work, form the basis for forecasting eruptions2014where, when, how big, how long, and the consequences. Accurate forecasts of the likelihood and magnitude of an eruption in a specified timeframe are rooted in a scientific understanding of the processes that govern the storage, ascent, and eruption of magma. Yet our understanding of volcanic systems is incomplete and biased by the limited number of volcanoes and eruption styles observed with advanced instrumentation. Volcanic Eruptions and Their Repose, Unrest, Precursors, and Timing identifies key science questions, research and observation priorities, and approaches for building a volcano science community capable of tackling them. This report presents goals for making major advances in volcano science.

Next Generation Earth System Prediction: Strategies for Subseasonal to Seasonal Forecasts - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
As the nation's economic activities, security concerns, and stewardship of natural resources become increasingly complex and globally interrelated, they become ever more sensitive to adverse impacts from weather, climate, and other natural phenomena. For several decades, forecasts with lead times of a few days for weather and other environmental phenomena have yielded valuable information to improve decision-making across all sectors of society. Developing the capability to forecast environmental conditions and disruptive events several weeks and months in advance could dramatically increase the value and benefit of environmental predictions, saving lives, protecting property, increasing economic vitality, protecting the environment, and informing policy choices. Over the past decade, the ability to forecast weather and climate conditions on subseasonal to seasonal (S2S) timescales, i.e., two to fifty-two weeks in advance, has improved substantially. Although significant progress has been made, much work remains to make S2S predictions skillful enough, as well as optimally tailored and communicated, to enable widespread use. Next Generation Earth System Predictions presents a ten-year U.S. research agenda that increases the nation's S2S research and modeling capability, advances S2S forecasting, and aids in decision making at medium and extended lead times.

Frontiers in Decadal Climate Variability: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Many factors contribute to variability in Earth's climate on a range of timescales, from seasons to decades. Natural climate variability arises from two different sources: (1) internal variability from interactions among components of the climate system, for example, between the ocean and the atmosphere, and (2) natural external forcings, such as variations in the amount of radiation from the Sun. External forcings on the climate system also arise from some human activities, such as the emission of greenhouse gases (GHGs) and aerosols. The climate that we experience is a combination of all of these factors. Understanding climate variability on the decadal timescale is important to decision-making. Planners and policy makers want information about decadal variability in order to make decisions in a range of sectors, including for infrastructure, water resources, agriculture, and energy. In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine variability in Earth's climate on decadal timescales, defined as 10 to 30 years. During the workshop, ocean and climate scientists reviewed the state of the science of decadal climate variability and its relationship to rates of human-caused global warming, and they explored opportunities for improvement in modeling and observations and assessing knowledge gaps. Frontiers in Decadal Climate Variability summarizes the presentations and discussions from the workshop.

Frontiers in Soil Science Research: Report of a Workshop - National Research Council (The National Academies Press, 2009)
There has been renewed interest in soil and soil science in recent years as the recognition that biogeochemical processes that occur at the Earth's surface influence global climate change, land degradation and remediation, the fate and transport of nutrients and contaminants, soil and water conservation, soil and water quality, food sufficiency and safety, and many other issues pertinent to the stewardship and conservation of land and water resources. In some areas of the Earth we have approached near irreversible soil conditions that may threaten the existence of future generations. Understanding the long-term implications of decreased soil quality and addressing the aforementioned challenges will require new information based on advances and breakthroughs in soil science research that need to be effectively communicated to stakeholders, policy makers, and the general public. On December 12-14, 2005, the National Academies convened the Frontiers in Soil Science Research Workshop, summarized in this volume, to identify emerging areas for research in soil science by addressing the interaction of soil science subdisciplines, collaborative research with other disciplines, and the use of new technologies in research. The workshop focused around seven key questions addressing research frontiers for the individual soil science disciplines, and also addressing the need for integration across soil science with other disciplines.

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere. These changes have led to major challenges for society, including deleterious impacts on climate, human and ecosystem health. Climate change is one of the greatest environmental challenges facing society today. Air pollution is a major threat to human health, as one out of eight deaths globally is caused by air pollution. And, future food production and global food security are vulnerable to both global change and air pollution. Atmospheric chemistry research is a key part of understanding and responding to these challenges. The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow summarizes the rationale and need for supporting a comprehensive U.S. research program in atmospheric chemistry; comments on the broad trends in laboratory, field, satellite, and modeling studies of atmospheric chemistry; determines the priority areas of research for advancing the basic science of atmospheric chemistry; and identifies the highest priority needs for improvements in the research infrastructure to address those priority research topics. This report describes the scientific advances over the past decade in six core areas of atmospheric chemistry: emissions, chemical transformation, oxidants, atmospheric dynamics and circulation, aerosol particles and clouds, and biogeochemical cycles and deposition. This material was developed for the NSF's Atmospheric Chemistry Program; however, the findings will be of interest to other agencies and programs that support atmospheric chemistry research.

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial. A growing body of research on coral physiology, ecology, molecular biology, and responses to stress has revealed potential tools to increase coral resilience. Some of this knowledge is poised to provide practical interventions in the short-term, whereas other discoveries are poised to facilitate research that may later open the doors to additional interventions. A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs reviews the state of science on genetic, ecological, and environmental interventions meant to enhance the persistence and resilience of coral reefs. The complex nature of corals and their associated microbiome lends itself to a wide range of possible approaches. This first report provides a summary of currently available information on the range of interventions present in the scientific literature and provides a basis for the forthcoming final report.

Integrating Social and Behavioral Sciences Within the Weather Enterprise - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Our ability to observe and forecast severe weather events has improved markedly over the past few decades. Forecasts of snow and ice storms, hurricanes and storm surge, extreme heat, and other severe weather events are made with greater accuracy, geographic specificity, and lead time to allow people and communities to take appropriate protective measures. Yet hazardous weather continues to cause loss of life and result in other preventable social costs. There is growing recognition that a host of social and behavioral factors affect how we prepare for, observe, predict, respond to, and are impacted by weather hazards. For example, an individual's response to a severe weather event may depend on their understanding of the forecast, prior experience with severe weather, concerns about their other family members or property, their capacity to take the recommended protective actions, and numerous other factors. Indeed, it is these factors that can determine whether or not a potential hazard becomes an actual disaster. Thus, it is essential to bring to bear expertise in the social and behavioral sciences (SBS)2014including disciplines such as anthropology, communication, demography, economics, geography, political science, psychology, and sociology2014to understand how people's knowledge, experiences, perceptions, and attitudes shape their responses to weather risks and to understand how human cognitive and social dynamics affect the forecast process itself. Integrating Social and Behavioral Sciences Within the Weather Enterprise explores and provides guidance on the challenges of integrating social and behavioral sciences within the weather enterprise. It assesses current SBS activities, describes the potential value of improved integration of SBS and barriers that impede this integration, develops a research agenda, and identifies infrastructural and institutional arrangements for successfully pursuing SBS-weather research and the transfer of relevant findings to operational settings.

Attribution of Extreme Weather Events in the Context of Climate Change - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
As climate has warmed over recent years, a new pattern of more frequent and more intense weather events has unfolded across the globe. Climate models simulate such changes in extreme events, and some of the reasons for the changes are well understood. Warming increases the likelihood of extremely hot days and nights, favors increased atmospheric moisture that may result in more frequent heavy rainfall and snowfall, and leads to evaporation that can exacerbate droughts. Even with evidence of these broad trends, scientists cautioned in the past that individual weather events couldn't be attributed to climate change. Now, with advances in understanding the climate science behind extreme events and the science of extreme event attribution, such blanket statements may not be accurate. The relatively young science of extreme event attribution seeks to tease out the influence of human-cause climate change from other factors, such as natural sources of variability like El Niño, as contributors to individual extreme events. Event attribution can answer questions about how much climate change influenced the probability or intensity of a specific type of weather event. As event attribution capabilities improve, they could help inform choices about assessing and managing risk, and in guiding climate adaptation strategies. This report examines the current state of science of extreme weather attribution, and identifies ways to move the science forward to improve attribution capabilities.

Environmental Engineering for the 21st Century: Addressing Grand Challenges - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Environmental engineers support the well-being of people and the planet in areas where the two intersect. Over the decades the field has improved countless lives through innovative systems for delivering water, treating waste, and preventing and remediating pollution in air, water, and soil. These achievements are a testament to the multidisciplinary, pragmatic, systems-oriented approach that characterizes environmental engineering. Environmental Engineering for the 21st Century: Addressing Grand Challenges outlines the crucial role for environmental engineers in this period of dramatic growth and change. The report identifies five pressing challenges of the 21st century that environmental engineers are uniquely poised to help advance: sustainably supply food, water, and energy; curb climate change and adapt to its impacts; design a future without pollution and waste; create efficient, healthy, resilient cities; and foster informed decisions and actions.

Progress Toward Restoring the Everglades: The Seventh Biennial Review - 2018 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure that was intended to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. Over the past two years, impressive progress has been made in planning new CERP projects, and the vision for CERP water storage is now becoming clear. Construction and completion of authorized CERP projects will likely take several decades, and at this pace of restoration, it is even more imperative that agencies anticipate and design for the Everglades of the future. This seventh biennial review assesses the progress made in meeting the goals of the CERP and provides an in-depth review of CERP monitoring, with particular emphasis on project-level monitoring and assessment. It reviews developments in research and assessment that inform restoration decision making, and identifies issues for in-depth evaluation considering new CERP program developments, policy initiatives, or improvements in scientific knowledge that have implications for restoration progress.

Understanding the Long-Term Evolution of the Coupled Natural-Human Coastal System: The Future of the U.S. Gulf Coast - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The U.S. Gulf Coast provides a valuable setting to study deeply connected natural and human interactions and feedbacks that have led to a complex, interconnected coastal system. The physical landscape in the region has changed significantly due to broad-scale, long-term processes such as coastal subsidence and river sediment deposition as well as short-term episodic events such as hurricanes. Modifications from human activities, including building levees and canals and constructing buildings and roads, have left their own imprint on the natural landscape. This coupled natural-human coastal system and the individual aspects within it (physical, ecological, and human) are under increased pressure from accelerating environmental stressors such as sea level rise, intensifying hurricanes, and continued population increase with its accompanying coastal development. Promoting the resilience and maintaining the habitability of the Gulf Coast into the future will need improved understanding of the coupled natural-human coastal system, as well as effective sharing of this understanding in support of decision-making and policies. Understanding the Long-term Evolution of the Coupled Natural-Human Coastal System presents a research agenda meant to enable a better understanding of the multiple and interconnected factors that influence long-term processes along the Gulf Coast. This report identifies scientific and technical gaps in understanding the interactions and feedbacks between human and natural processes, defines essential components of a research and development program in response to the identified gaps, and develops priorities for critical areas of research.

A Decision Framework for Managing the Spirit Lake and Toutle River System at Mount St. Helens - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The 1980 eruption of Mount St. Helens in southwest Washington State radically changed the physical and socio-economic landscapes of the region. The eruption destroyed the summit of the volcano, sending large amounts of debris into the North Fork Toutle River, and blocking the sole means of drainage from Spirit Lake 4 miles north of Mount St. Helens. As a result of the blockage, rising lake levels could cause failure of the debris blockage, putting the downstream population of approximately 50,000 at risk of catastrophic flooding and mud flows. Further, continued transport of sediment to the river from volcanic debris deposits surrounding the mountain reduces the flood carrying capacity of downstream river channels and leaves the population vulnerable to chronic flooding. The legacy of the 1980 eruption and the prospect of future volcanic, seismic, and flood events mean that risk management in the Spirit Lake Toutle River system will be challenging for decades to come. This report offers a decision framework to support the long-term management of risks related to the Spirit Lake and Toutle River system in light of the different regional economic, cultural, and social priorities, and the respective roles of federal, tribal, state, and local authorities, as well as other entities and groups in the region. It also considers the history and adequacy of characterization, monitoring, and management associated with the Spirit Lake debris blockage and outflow tunnel, other efforts to control transport of water and sediment from the 1980 and later eruptions, and suggests additional information needed to support implementation of the recommended decision framework.

Negative Emissions Technologies and Reliable Sequestration: A Research Agenda - National Academies of Sciences, Engineering,; Medicine
To achieve goals for climate and economic growth, \

Improving Characterization of Anthropogenic Methane Emissions in the United States - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Understanding, quantifying, and tracking atmospheric methane and emissions is essential for addressing concerns and informing decisions that affect the climate, economy, and human health and safety. Atmospheric methane is a potent greenhouse gas (GHG) that contributes to global warming. While carbon dioxide is by far the dominant cause of the rise in global average temperatures, methane also plays a significant role because it absorbs more energy per unit mass than carbon dioxide does, giving it a disproportionately large effect on global radiative forcing. In addition to contributing to climate change, methane also affects human health as a precursor to ozone pollution in the lower atmosphere. Improving Characterization of Anthropogenic Methane Emissions in the United States summarizes the current state of understanding of methane emissions sources and the measurement approaches and evaluates opportunities for methodological and inventory development improvements. This report will inform future research agendas of various U.S. agencies, including NOAA, the EPA, the DOE, NASA, the U.S. Department of Agriculture (USDA), and the National Science Foundation (NSF).